2020
DOI: 10.1098/rsta.2019.0389
|View full text |Cite
|
Sign up to set email alerts
|

Flood resilience, amenity and biodiversity benefits of an historic urban pond

Abstract: The main pond within the historic Royal Botanic Garden Edinburgh is an important component of urban blue-green infrastructure. This paper reports on flood resilience provided by the pond (simulated using the CityCAT hydrodynamic model), its water residence times (obtained using the Shetran hydrological model), and the ecology and biodiversity (vascular plants, bryophytes, aquatic invertebrates, phyto- and zooplankton, birds) of the pond and the adjacent area. The results show that the pond improves the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 35 publications
3
12
0
Order By: Relevance
“…The research presented here highlights the importance of ecosystem services provided by the SuDS ponds studied and gives an account of their hydrology, ecology and water quality, as well as an insight into further multiple benefits associated with amenity and biodiversity values. The results are in line with other studies demonstrating that BGI pond sites provide an increase in flood resilience and improvements in water quality as well as aid to the creation of wildlife corridors, thus contributing to the enhancement of urban biodiversity [9].…”
Section: Discussion and Concluding Remarkssupporting
confidence: 92%
See 2 more Smart Citations
“…The research presented here highlights the importance of ecosystem services provided by the SuDS ponds studied and gives an account of their hydrology, ecology and water quality, as well as an insight into further multiple benefits associated with amenity and biodiversity values. The results are in line with other studies demonstrating that BGI pond sites provide an increase in flood resilience and improvements in water quality as well as aid to the creation of wildlife corridors, thus contributing to the enhancement of urban biodiversity [9].…”
Section: Discussion and Concluding Remarkssupporting
confidence: 92%
“…These environmental factors mirror those of the only other known Lothians site, adjacent to Inverleith House in the Royal Botanic Garden Edinburgh. Hence despite its small size, this SuDS asset provides a very important contribution to the local biodiversity, which is in line with other studies on the Edinburgh BGI ponds [9].…”
Section: Further Amenity and Biodiversity Benefitssupporting
confidence: 90%
See 1 more Smart Citation
“…We also found that the water bodies in our study are not round; some had roundness akin to that of an isosceles triangle (0.78), including Windsor, CA (0.78), and Walden, CO (0.79), and the least round is Orlando, FL (0.67). Across broader datasets of FPVs, understanding the shape of the recipient water bodies for FPVs may serve to, in part, identify FPV sites where biodiversity is most likely to intersect with FPV development, especially in urban water bodies which serve as critical refugia for biodiversity and support diverse ecosystem services to local communities [78,79].…”
Section: Technohydrological and Spatial Attributes Of Fpvsmentioning
confidence: 99%
“…We found that the FPVs were very similar in compactness, ranging from 0.68 to 0.76. Ultimately, the shape of an FPV may be driven by not only equipment design standards by the FPV manufacturer (compactness did vary across FPVs by Ciel et Terre©), but also sizing optimization to satisfy demand load, water body attributes (shape, water quality, biodiversity), water body co-use needs and values (flood resilience, recreation, education, visual amenity), meter accessibility, and others, which should be further explored [79]. These factors likely also play a role in determining the amount of water surface covered by panels that, unlike compactness, we found varied strikingly across the four FPVs from 3.1 to 69.8%.…”
Section: Technohydrological and Spatial Attributes Of Fpvsmentioning
confidence: 99%